Indirect orthodontic bonding - a modified technique for improved efficiency and precision - Nojima,Lincoln Issamu (2015)
INTRODUCTION: The indirect bonding technique optimizes fixed appliance installation at the orthodontic office, ensuring precise bracket positioning, among other advantages. In this laboratory clinical phase, material and methods employed in creating the transfer tray are decisive to accuracy. OBJECTIVE: This article describes a simple, efficient and reproducible indirect bonding technique that allows the procedure to be carried out successfully. Variables influencing the orthodontic bonding are analyzed and discussed in order to aid professionals wishing to adopt the indirect bonding technique routinely in their clinical practice.